2019
DOI: 10.1016/j.phro.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with lung-specific electromagnetic transponders for real-time tumor tracking in lung stereotactic body radiotherapy

Abstract: Background and purposes: Motion management is crucial for optimal stereotactic body radiotherapy (SBRT) of moving targets. We aimed to describe our clinical experience with real-time tracking of lung-specific electromagnetic transponders (EMTs) for SBRT of early stage non-small cell lung cancer in free-breathing (FB) or deep inspiration breath-hold (DIBH). Material and methods: Seven patients were implanted with EMTs. Simulation for SBRT was performed in FB and in DIBH. We prescribed 60 Gy in 3, 5 or 8 fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…These studies found that EMTs can be used for monitoring and tracking during treatment and that EMTs are stable and do not migrate. One of these clinical studies evaluated four stereotactic body radiation therapy (SBRT) patients treated in DIBH and three patients treated in free breathing and found that the EMT positions in the lungs remained stable during treatment by using on‐treatment verification CBCTs to visualize whether the EMTs had good alignment with other structures 32 . The other clinical studies were performed using patients treated with free breathing only, with one study using breath‐hold CT images acquired before treatment and periodically throughout to assess whether the EMTs were stable 39 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that EMTs can be used for monitoring and tracking during treatment and that EMTs are stable and do not migrate. One of these clinical studies evaluated four stereotactic body radiation therapy (SBRT) patients treated in DIBH and three patients treated in free breathing and found that the EMT positions in the lungs remained stable during treatment by using on‐treatment verification CBCTs to visualize whether the EMTs had good alignment with other structures 32 . The other clinical studies were performed using patients treated with free breathing only, with one study using breath‐hold CT images acquired before treatment and periodically throughout to assess whether the EMTs were stable 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Each patient had three lung electromagnetic beacons (Calypso, Varian Medical Systems, Palo Alto, CA) implanted endobronchially under fluoroscopic guidance. 5,22 The lung specific beacons incorporated the electromagnetic beacons along with three prongs, which were embedded into the airway wall during insertion to minimize migration. Planning for implantation was performed using a preimplant CT scan with the aim that all beacons were inserted as close as possible to the tumor, while attempting to form a triangle in three dimensions around the tumor.…”
Section: Methodsmentioning
confidence: 99%
“… 3D and 4D imaging (cone beam CT-CBCT).  Newer technologies including imaging and monitoring of electromagnetic transponders (55)(56)(57) or small fiducial markers inserted near the tumor and visible on X-rays or CBCT (58)(59)(60)(61)(62).  Lately surface guidance is used for verification and monitoring of the patient set-up (63,64).…”
Section: Verification Of the Patient Positioning And Target Locationmentioning
confidence: 99%